Contribution to a reference library of DNA barcodes of Colombian freshwater fishes (2022)
ABSTRACT: The Barcode of Life initiative was originally motivated by the large number of species, taxonomic difficulties and the limited number of expert taxonomists. Colombia has 1,610 freshwater fish species and comprises the second largest diversity of this group in the world. As genetic information continues to be limited, we constructed a reference collection of DNA sequences of Colombian freshwater fishes deposited in the Ichthyology Collection of the University of Antioquia (CIUA), thus joining the multiple efforts that have been made in the country to contribute to the knowledge of genetic diversity in order to strengthen the inventories of biological collections and facilitate the solution of taxonomic issues in the future.